Evaluation of androgen-dependent skin findings of polycystic ovary syndrome (PCOS). (2nd December 2022) - Artar, Gokhan; Tas, Betul; Turan, Gokce; Uckan, Hasan Huseyin
Abstract: Aim: The purpose of the study was to investigate the biochemical and metabolic abnormalities related to the cutaneous characteristics of PCOS. Material–Methods: Patients diagnosed with PCOS were included in the study. Demographic data and accompanying androgen-dependent skin findings (acne, seborrhea, androgenic alopecia, acanthosis nigricans, skin tag, and hirsutism) were recorded. The free testosterone, total testosterone, dehydroepiandrosterone sulfate, androstenedione, 17-Hidroksi progesterone, sex hormone binding globulin, prolactin, fasting glucose, fasting insulin, HbA1C, HDL, and triglycerides, follicle-stimulating hormone, luteinized hormone, free androgen index, and HOMA-IR levels of the patients were measured. The hormonal values of the patients with PCOS with and without skin findings were compared. Results: The HOMA-IR values of the acanthosis nigricans (+) PCOS group were significantly higher than the acanthosis nigricans (–) PCOS group ( p  < .001). The DHEA-SO4, FAI, and FI values of patients with hirsutism (HR) (+) PCOS were found to be statistically higher than patients with HR (–) PCOS ( p  = .006, p  = .015, p  = .004). Conclusion: PCOS is among the most common endocrine disorders of women of reproductive age and was associated with some hormonal, metabolic, and skin findings. Certain androgenic and metabolic variables developing in PCOS might correlate with cutaneous symptoms.